Human Character Based on Ki Ageng Suryomentaram Teachings and Its Implementation in Guidance and Counseling Services - Habsy, Bakhrudin All; Kurniawan, Nanda Alfan (Jurnal Kajian Bimbingan dan Konseling, 2024)
The Indonesian nation as a large nation consisting of various religions, ethnicities, and cultures, of course, deserves to have the aspiration to have a basic human philosophy paradigm based on Indonesian culture based on dialogue between the soul sciences that live in Indonesian human cognition. This study aims to present the concept of basic human philosophy in the teachings of Ki Ageng Suryomentaram. The research method uses Gadamerian hermeneutics in a qualitative approach. The collected data is then analyzed using Parts and Whole analysis and then checked the validity of the data through the stages of credibility, transferability, dependability, and confirmability. The results of the study describe human philosophy based on basic needs, essence, existence, and the structure of the human personality. The conclusion of the research refers to the basic human philosophy based on local wisdom for the science of guidance and counseling.